Criminal law mechanism for countering economic smuggling: status and problems - Seilkhanov, Ж.Д.; Shabanov, В.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
Economic smuggling constitutes one of the most serious threats to a state’s economic security, causing damage to financial interests and undermining the stability of law and order. The article examines issues related to improving the criminal law regulation of liability for economic smuggling in the Republic of Kazakhstan, with particular emphasis on Article 234 of the Criminal Code of the Republic of Kazakhstan. The purpose of the study is to develop scientifically grounded proposals aimed at enhancing the effectiveness of countering economic smuggling, safeguarding national interests, and preventing the illegal movement of goods across the customs border of the Eurasian Economic Union and the State border of the Republic of Kazakhstan. The study analyzes the provisions of criminal legislation and judicial practice, identifying key problems in law enforcement. Special attention is given to the differentiation of criminal liability depending on the nature and degree of public danger, including repeated commission of the offense, its perpetration by a group of persons by prior conspiracy, abuse of official position, as well as commission on a large or especially large scale. The scientific significance of the research lies in clarifying approaches to defining the limits of criminal liability and formulating proposals for their improvement. The practical significance is reflected in the possibility of applying the findings in legislative development and in the activities of law enforcement agencies. The methodological framework of the study includes general scientific methods of analysis and synthesis, formal-legal and comparative-legal methods, as well as the examination of judicial practice materials. The study substantiates the need to strengthen criminal liability, including increasing terms of imprisonment and the amount of fines. It also proposes stricter measures for officials and members of organized criminal groups involved in economic smuggling. The conclusion is drawn that punishment should be differentiated depending on the method of committing the offense and the severity of its consequences. The results contribute to improving the legal mechanism for combating economic smuggling.